Kajian Kritik pada Bentuk dan Pengaruh Positif al-Dakhil dalam Tafsir Jalalain tentang Kisah Nabi Musa dan Khidir - Andri Nirwana; Ita Purnama Sari; Suharjianto Suharjianto; Syamsul Hidayat (Institut Agama Islam Negeri (IAIN) Curup, 2021)
A Study of Criticism on the Forms and Positive Effects of al-Dakhil in Jalalain's Tafsir of the Story of Prophet Musa and KhidirIn the tafseer, Al-dakhil is the inclusion of baseless interpretation into the book of tafseer. Thebaseless inclusion to interpretations is motivated by several of elements israiliyyat, hadis da’if, hadis maudu’, baseless ta’wil or interpretations which defend to the interest of a certain groups or madzab. Al-dakhil in the tafseer was exist since Prophet era and has been sphreading until now. The effect of al-dakhil in to tafseer are can lead to the assumption that Islamic religion are no longer authentic (bias), the unificationof Islamic and other doctrine, and the aumption that the Al-Qur’an is a book in which there are many tahayyul and khurafat. The aim of this research is to find what is the kind of Al-Dakhil in the Jalalain’s Tafsir surah al-Kahfi verses 60-82. This is a qualitative research that uses an interpretive criticism approach, which aims to determine the authenticity of text, then it is analyzed using descriptive-analysis methods to describe the results of research that was found.The result of this research is that the kind of al-dakhil that contained in the Jalalain Tafseer Chapter Al-Kahfi verses 60-82 is al-dakhil bi al-ma’tsur with the type of israiliyyat found in the story: prophet Khidhir have had killed a child while debark from a boat; the story name of the country visited by Musa and Khidhir with his son and the walls of house are hundred cubits heights the story of the boat owner working at marine are ten persons; the story of substitute child who was killed is a woman who married with the Prophet, then gave birth a prophet and Allah made him a guide for people; and story of the treasures of two orphans were gold and silver. From this research, it was expected become an academic contribution, in the scientific of Al-Qur’an and Tafseer, especially on the theme al-dakhil fi al-tafsir